Mwenda Ntarangwi, David Mills and Mustafa Babiker (eds). African Anthropologies: History, Critique and Practice - Kallinen, Timo (Suomen Antropologi, 2009)
M WENDA NTARANGWI , D AVID M ILLS AND M USTAFA B ABIKER (eds). African Anthropologies: History, Critique and Practice. Dakar: Codesria, 2006. Pp. 274. ISBN: 978-1-84277-763-3